Sikap Ibu tentang Pencegahan Gigi Karies pada Anak Pra Sekolah dI TK AL-QODIRI Kabupaten Jember - Ayu Puteri Nur Perdani (Jurnal MID-Z (MIDWIFERI ZIGOT), 2018)
Dental caries is a tooth tissue damage that results in cavities. Increased prevalence of caries is influenced by changes in diet, as well as daily toothbrush patterns. Based on a preliminary survey conducted by researchers on 12 February 2013 in Al-Qodiri Jember Kindergarten for 32 children aged 3 - 5 years, 25 students had caries and 7 students did not experience caries. As well as from the interview I did on 7 mothers of 32 mothers who had children aged 3 - 5 years who attended Al-Qodiri Jember Kindergarten they said they did not care about the food their children ate and did not tell their children to brush their teeth before going to bed and after eat. This study aims to determine the attitude of mothers about prevention of caries teeth in pre-school children in TK Al-Qodiri Jember.The design of this study is a descriptive survey approach. The population is all mothers who have children aged 3-5 years who attend 36 Al-Qodiri Jember Kindergarten and 3-5 years old students totaling 32 students. The sampling technique used is total sampling. the variable is the mother's attitude about prevention of caries teeth in pre-school children. While the instruments used in data collection are questionnaires. Data processing editing, coding, scoring, tabulating and data analysis. Based on the results of this study it was found that maternal attitudes about the prevention of negative caries teeth were 17 respondents and those who were positive were 15 respondents. Conclusions from the results of this study that maternal attitudes about prevention of caries teeth in pre-school children in Al-Qodiri Jember Kindergarten with the criteria of maternal attitudes about prevention of caries teeth in pre-school children were negative. It is expected that mothers discipline their children in brushing their teeth before going to bed and after eating and reducing sweet and sticky foods that can cause dental caries in pre-school age children.